(untitled) (Fiep Bulletin - online, 2015)
Leisure can be used as a multiple possibility of visualizing the local society and urban life. It is necessary to think of leisure as a symbol, a new reference to civilization, a representation, from the end of the XIX century and the beginning of the XX century. In order to identify leisure as a strategic element for knowing society, it is necessary to understand its meaning, analyzing it through a long duration process, which has its beginning in a multidisciplinary view, that is, in a combination of sociological, psychological and historical aspects. The leisure activities done in a socially limited way, allow emotional experiences that usually are not lived in routine activities. Leisure activities are part of an activity category in which the emotion routine restriction can be publicly reduced and with social approval, more than any other. The individual can enjoy pleasant emotions, without endangering others and himself. But the risk component is present, making part of pleasure, and through it, it is possible to challenge the rules of a routine life (up to a determined limit). What did leisure mean to all the people who lived in Brazilian cities in the end of the XIX century and beginning of the XX century, and mainly in the city of Curitiba? Curitiba, which began to be modernized, part due to the presence of immigrants, but also due to the initiative taken by its administrators. In the leisure area, theater was a great success, with the competition of the first cinemas, the building of parks and squares answered the necessity of fun and pleasure for the population. Curitiba now offered conditions for a more sophisticated social and cultural life. It was in this “new” city that Curitibano Club appeared and influenced the local society.